2015
DOI: 10.20450/mjcce.2015.629
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic dopants in polymer cholesteric liquid crystals

Abstract: <p>A variety of dopants are used for different types of polymers to change their properties. Inorganic dopants are usually used to change the dielectric properties of the polymers. These compositions find different applications especially in electronic systems due to ease of polymer processing, increased functionality and low cost of novel materials that are with relatively high dielectric constant compared to the base polymer material.</p><p>In this study, polymer cholesteric liquid crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…N. Guo et al synthesized nanocomposites and observed that rodshaped nanofillers exhibited a higher dielectric con-stant than the nanocomposite prepared using spherical nanofillers [16]. A research study has reported on that needle-shaped TiO 2 fillers increased the dielectric constant more than the spherically shaped TiO 2 fillers, when composed with polymeric cholesteric liquid crystals at a lower volume than spherical ones [42]. Another investigation reported on that, as the filler size was reduced to the nano scale, the dielectric loss increased effectively as nanoparticles exhibited a tendency to agglomerate.…”
Section: Filler Size and Shapementioning
confidence: 99%
“…N. Guo et al synthesized nanocomposites and observed that rodshaped nanofillers exhibited a higher dielectric con-stant than the nanocomposite prepared using spherical nanofillers [16]. A research study has reported on that needle-shaped TiO 2 fillers increased the dielectric constant more than the spherically shaped TiO 2 fillers, when composed with polymeric cholesteric liquid crystals at a lower volume than spherical ones [42]. Another investigation reported on that, as the filler size was reduced to the nano scale, the dielectric loss increased effectively as nanoparticles exhibited a tendency to agglomerate.…”
Section: Filler Size and Shapementioning
confidence: 99%